Relationship between the value of the estrous detector measurement result and serum progesterone level in Etawa crossbred goats after estrous synchronization - Triagil, Annisa Lita; Ismudiono, Ismudiono; Lestari, Tita Damayanti; Samik, Abdul; Utomo, Budi; Setiawan, Boedi (Ovozoa: Journal of Animal Reproduction, 2020)
This study was conducted to determine the relationship between the estrous detector's reading value (Draminski®, DramiÅ„ski S.A, Poland) and serum progesterone levels on Etawa crossbred does. Eighteen healthynon-prehnant Etawa crossbreds does weighing 20-25 kg, in their first parity were used in this study. The does were divided equally into two groups. In the two groups, the does were synchronized their estrus by means of intramuscular and intravulvar injection of 7.5 mg prostaglandin FÉ‘ (PGF2É‘) twice in 11-day intervals. After the second injection, the estrous detector value measurement, visual observation of the estrus sign, and blood sampling were conducted for five days. The blood sample was processed into the serum to examine for progesterone levels by ELISA. The data analysis was using the simple correlation method on SPSS type 23 for windows. The result showed that a positive relationship (p <0.05) with coefficient correlation (r) was 0.609 between the values of the estrous detector measurement with serum progesterone levels. It could be concluded that the estrous detector's low value indicates that the Etawa crossbred was in the estrus phase and followed by the decreasing of progesterone level but not reaching the basal level.